PENGARUH AUDIT FEE, REPUTASI AUDITOR, ROTASI AUDITOR TERHADAP KUALITAS AUDIT PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Wahyu Setiawan; Masrullah, Sahrullah (Jurnal Ekonomi dan Bisnis, 2025)
This research aims to determine the influence of Audit Fees, Auditor Reputation, Auditor Rotation on Audit Quality in Banking companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The data in this research was obtained from company financial reports which were accessed via the website www.idx.co.id. The data analysis technique used is quantitative descriptive analysis with Logistic Regression analysis. This research is a type of quantitative research using the Purposive Sampling method. The sample in this study consisted of 32 banking companies, data processing used SPSS 29 software. The results of this study showed that Audit Fees had a significant positive effect on Audit Quality, Auditor Reputation had a significant negative effect on Audit Quality, Auditor Rotation had no effect on Audit Quality.